Dampak Kemiskinan Terhadap Penyimpangan Sisoal Pada Remaja Di Kelurahan Talang Betutu Kecamatan Sukarami Kota Palembang - Suryati Suryati; Muzaiyanah Muzaiyanah; Suryadi Suryadi (Journal of Innovative and Creativity, 2025)
This study aims to determine the impact of poverty on social deviation in adolescents in Talang Betutu Village, Sukarami District, Palembang City. The purpose of this study is to determine how the impact of poverty becomes the main factor or the beginning of social deviation. This study is a descriptive field study, namely describing several data findings formulated in the form of words. The author took sample data using purposive sampling. Based on the criteria provided by the author, the sample numbered 5 people. The tools used by the author to collect data were the results of documentation, observation, and interviews. The results of this study indicate that the impact of poverty is the beginning of social deviation in Talang Betutu Village in addition to other factors that influence it. Therefore, economic fulfillment is the main goal for oneself or a group to get a decent life, food, drink, clothing, education and so on that concern the quality of life and social life of a person. The conclusion from the results of this study is that poverty is based on culture and can give birth to deviations in the form of theft, mugging, use and distribution of illegal drugs, and lifestyle demands. Then it is proven that the impact of poverty is the beginning of social deviation in Talang Betutu Village in addition to other factors that influence it. These things are strengthened by the five respondents who showed that poverty led them to the path of social deviation, namely in the scope of criminality.